RELATIONSHIPS BETWEEN LANGUAGE UNITS AND THEORY OF VALENCE (Eureka Journal of Language, Culture & Social Change, 2026)
"Relationships" are understood as the relationships and connections between the components of a whole - units. Such relationships can be of various kinds. Similarities and differences in form, meaning, or function are the most basic forms of relationships and connections between language units.
Keywords: Paradigmatic, hierarchical, syntagmatic relations, language units, syntactic relations, level, associative relations.